Interactions between epinephrine, ascending vagal fibers, and central noradrenergic systems in modulating memory for emotionally arousing events - Williams, Cedric L. (Frontiers in Behavioral Neuroscience, 2012)
It is well established that exposure to emotionally laden events initiates secretion of the arousal related hormone epinephrine in the periphery. These neuroendocrine changes and the subsequent increase in peripheral physiological output play an integral role in modulating brain systems involved in memory formation. The impermeability of the blood brain barrier to epinephrine represents an important obstacle in understanding how peripheral hormones initiate neurochemical changes in the brain that lead to effective memory formation. This obstacle necessitated the identity of a putative pathway capable of conveying physiological changes produced by epinephrine to limbic structures that incorporate arousal and affect related information into memory. A major theme of the proposed studies is that ascending fibers of the vagus nerve may represent such a mechanism. This hypothesis was tested by evaluating the contribution of ascending vagal fibers in modulating memory for responses learned under behavioral conditions that produce emotional arousal by manipulating appetitive stimuli. A combination of electrophysiological recording of vagal afferent fibers and in vivo microdialysis was employed in a second study to simultaneously assess how elevations in peripheral levels of epinephrine affect vagal nerve discharge and the subsequent potentiation of norepinephrine release in the basolateral amygdala. The final study used double immunohistochemistry labeling of c-fos and dopamine beta hydroxylase, the enzyme for norepinephrine synthesis to determine if epinephrine administration alone or stimulation of the vagus nerve at an intensity identical to that which improved memory in Experiment 1 produces similar patterns of neuronal activity in brain areas involved in processing memory for emotional events. Findings emerging from this collection of studies establish the importance of ascending fibers of the vagus nerve as an essential pathway for conveying the peripheral consequence